Motion Characteristics and Kinematics of Fresh Spermatozoa of Gir, Surti and Murrah Bulls Assessed By Computer Assisted Semen Analyzer - Pathak, P.K.; Dhami, A.J.; Chaudhari , D.V.; Hadiya, K.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A study was carried out on semen of nine breeding bulls, three each of Gir, Surti and Murrah breeds, to evaluate the comparative motion characteristics and kinematics of their fresh spermatozoa by CASA. The ejaculates (n=72, 24 of each breed) having >75% initial motility were diluted @ 80 million sperm/ml using TFYG extender and were assessed for motion characteristics by CASA. The overall mean values of rapid motile and immotile sperm per cent were observed significantly greater in Gir bulls semen, while total motile and slow motile sperms were apparently higher in buffalo semen. The mean values of sperm velocity/ kinematic parameters observed based on all motile sperms in Gir, Surti and Murrah bulls semen were: average path velocity 50.01±1.25, 48.51±1.03 & 49.14±1.30 µm/s; curvilinear velocity 88.62±1.66, 87.90 ±1.74 & 88.93±1.69 µm/s, straight line velocity 44.51±1.35, 43.14±1.12 & 41.73±2.24 µm/s; linearity 50.06±1.42, 48.86±1.32 & 48.49±1.84 %; straightness 85.17±0.92, 84.97±0.88 & 83.90±1.17 %; wobbling index 57.00±1.17, 55.32±1.05 & 55.30±1.48 %; beat-cross frequency 15.55±0.58, 16.14±0.43 & 14.97±0.54 hz; amplitude of lateral head displacement 2.39±0.18, 2.57±0.12 & 2.31±0.14 µm; dancing frequency 208.34±15.52, 225.00 ±10.74 & 211.29±13.03 µm2/s, and dancing mean 5.70±0.46, 6.33±0.35 & 6.33±0.50 µm2/s, respectively. Almost similar trend with little higher values were noted for sperm velocity/kinematics based on only progressively motile sperm, without breed/species variation. The semen of all three breeds behaved identically for sperm kinematics. The bull variation was insignificant for all the traits in all the three breeds.
Keywords: Cow bull; Buffalo bull; Fresh semen; Motion characteristics; Sperm kinematics; CASA